Sheep models of F508del and G542X cystic fibrosis mutations show cellular responses to human therapeutics. Issue 10 (2nd August 2021) - Viotti Perisse, Iuri; Fan, Zhiqiang; Van Wettere, Arnaud; Liu, Ying; Leir, Shih‐Hsing; Keim, Jacob; Regouski, Misha; Wilson, Michael D.; Cholewa, Kelly M.; Mansbach, Sara N.; Kelley, Thomas J.; Wang, Zhongde; et al.
Abstract: Cystic Fibrosis (CF) is a genetic disease caused by mutations in the CF transmembrane conductance regulator ( CFTR ) gene. The F508del and G542X are the most common mutations found in US patients, accounting for 86.4% and 4.6% of all mutations, respectively. The F508del causes deletion of the phenylalanine residue at position 508 and is associated with impaired CFTR protein folding. The G542X is a nonsense mutation that introduces a stop codon into the mRNA, thus preventing normal CFTR protein synthesis. Here, we describe the generation of CFTR F508del / F508del and CFTR G542X / G542X lambs using CRISPR/Cas9 and somatic cell nuclear transfer (SCNT). First, we introduced either F508del or G542X mutations into sheep fetal fibroblasts that were subsequently used as nuclear donors for SCNT. The newborn CF lambs develop pathology similar to CFTR −/− sheep and CF patients. Moreover, tracheal epithelial cells from the CFTR F508del / F508del lambs responded to a human CFTR (hCFTR) potentiator and correctors, and those from CFTR G542X / G542X lambs showed modest restoration of CFTR function following inhibition of nonsense‐mediated decay (NMD) and aminoglycoside antibiotic treatments. Thus, the phenotype and electrophysiology of these novel models represent an important advance for testing new CF therapeutics and gene therapy to improve the health of patients with this life‐limiting disorder.